A revision of the Mexican Anolis (Reptilia, Squamata, Dactyloidae) from the Pacific versant west of the Isthmus de Tehuantepec in the states of Oaxaca, Guerrero, and Puebla, with the description of six new species: Addendum - Köhler, Gunther; Pérez, Raúl Gómez Trejo; Petersen, Claus Bo P.; de La Cruz, Fausto R. Méndez (Zootaxa, 2015)
In the published version of ‘A revision of the Mexican Anolis (Reptilia, Squamata, Dactyloidae) from the Pacific versant west of the Isthmus de Tehuantepec in the states of Oaxaca, Guerrero, and Puebla, with the description of six new species’ (Köhler et al., 2014) we failed to provide GenBank accession numbers for the sequences used in our study. This ommission is corrected below.